دراسة تجريبية لضياعات التهوية في علب السرعة - عبد الله, معالي (Latakia University Journal -Engineering Sciences Series, 2017)
تمت دراسة ضياعات الطاقة بالتهوية في المسننات المائلة عند السرعات العالية من خلال اختبار مجموعة من المسننات المصنوعة من خشب الزان بمواصفات هندسية معينة ، ولتحقيق ذلك صمم وطور جهاز اختبار لقياس ضياع التهوية بالمسننات..يتألف هذا الجهاز من محرك كهربائي ذو استطاعة ((3 kW يقوم بتدوير محور يرتكز على محملين دحروجيين عن طريق دولاب احتكاكي، حيث يركب الدولاب المسنن المختبر على أحد طرفي المحور في حين أن الطرف الحر الأخر تم تركيب حساس كهرومغناطيسي بحيث يقوم بقياس سرعة الدوران كتابع للزمن من خلال لوحة التحكم.يتم تحديد ضياع الطاقة بالتهوية الناتج عن المسنن من خلال طرح ضياع الطاقة الناتج عن تدوير المحور بمفرده من ضياع الطاقة الناتج عن تدوير الجملة (محور - مسنن) .بعد إجراء التجارب و الاختبارات يتم رسم المخططات لكل من الضياعين النظري و التجريبي ،ثم مقارنة الضياع النظري لكل مسنن مع الضياع التجريبي الذي حصلنا عليه من اختبار المسننات على جهاز الاختبار المصمم.The education of wasting energy by Windge in helical gears has achieved in high speed by testing a group of gears that made of beech in determined geometrical specifications. So a testing device is designed and developed to measure the Windge wasting energy in gears.This device is consists of electrical driver (3kw) that turning a pivot that leaned on two rolling carrier across a friction wheel. This indented friction wheel is ride in the end of pivot, while the other free end is supplied with electromagnetic sensor to measure the turning speed as a function of time across a control board. The Windge wasting energy is determined by minus the wasting energy that resulting from turning the pivot alone, from that resulting from turning the whole system (pivot-gear).After doing the tests and experiments, the patterns of the losing (theoretical losses, practical losses) is draw. Then a comparative between the theoretical losses and that has gotten from testing device.